2023
DOI: 10.7717/peerj.16045
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of the relationships between rice yield and climate variables since 1925

Hungyen Chen,
Yi-Chien Wu,
Chih-Yung Teng

Abstract: Background Long-term time-series datasets of crop yield and climate variables are necessary to study the temporal variation of climate effects on crops. The aim of this study was to broadly assess assessment of the effects of climate on rice, and the associated temporal variations of the effects during the long-term period. Methods We conducted field experiments in Taiwan from 1925 to 2019 to collect and analyze rice yield data and evaluate the impacts of changes in average temperature, diurnal temperature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…However, the aggregate data indicates that the daily sunshine hours in Trial 2 were significantly higher by 11.3% compared to Trial 1. Despite this, a study conducted in the same growing region (Taiwan) from 1925-2019 has demonstrated that the impact of sunshine duration on rice yield variations is relatively minor when compared to other climatic variables such as diurnal temperature range [67]. Therefore, any influence of daily sunshine hours on the growth and yield of rice in this study may have been minimal or negligible.…”
Section: Growing Environmental Conditionsmentioning
confidence: 74%
“…However, the aggregate data indicates that the daily sunshine hours in Trial 2 were significantly higher by 11.3% compared to Trial 1. Despite this, a study conducted in the same growing region (Taiwan) from 1925-2019 has demonstrated that the impact of sunshine duration on rice yield variations is relatively minor when compared to other climatic variables such as diurnal temperature range [67]. Therefore, any influence of daily sunshine hours on the growth and yield of rice in this study may have been minimal or negligible.…”
Section: Growing Environmental Conditionsmentioning
confidence: 74%